A Kindred with a β-Globin Base Substitution [β89(F5)Ser→Arg (AGT>AGG); HBB: c.270T>G] Resulting in Hemoglobin Vanderbilt. (3rd September 2019) - Shomali, William; Brar, Rondeep; Arekapudi, Subramanyeswara R.; Gotlib, Jason R.
Abstract: High oxygen affinity hemoglobins (Hbs), characterized by a decreased ability to release oxygen to the tissues and a left-shifted oxygen dissociation curve, are a rare cause of secondary erythrocytosis. Here, we report a base substitution in the β-globin gene at codon 89 (AG T >AG G ) in a kindred with familial erythrocytosis resulting in Hb Vanderbilt, a high oxygen affinity variant.